The Effect of Cross-Border Group Taxation on Ownership Chains. Issue 5 (20th October 2019) - Rünger, Silke
ABSTRACT: This study investigates the influence of taxation on ownership chains and specifically on the location decision for intermediate holding companies. By examining the effect of the introduction of a cross-border group taxation regime in Austria in 2005 on ownership chains of European multinational firms, I find evidence that foreign parent companies already invested in Austria restructured their ownership chains in order to meet the requirements of the group taxation regime. This effect is larger for foreign parent companies with loss-generating subsidiaries. Collectively, the empirical findings suggest that, when evaluating the effect of cross-border group taxation regimes, companies follow a detailed tax planning strategy that takes tax-base effects into account.